Answer:
8
I made a couple of assumptions so you might want to make sure I made the right assumptions.
I assumed you meant square root of z; not source of z.
I also assumed you meant x=2 not x=z.
Explanation:
y varies directly with means y=k times something where k is a constant.
Inversely means to divide by whatever it says it varies inversely with.
So we have:
![y=k \cdot (x)/(√(z))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f89nvqh0gjkvgkynj8kyxpka8ibfwkf2q4.png)
We are given y=4 and x=2 and z=4, which means:
![4=k \cdot (2)/(√(4))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ir20pvgeb226dssl8tnt6pj1yeoze5aelj.png)
![4=k \cdot (2)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y6gkl2p2rbczkt7cpz8ncorjbph0lk4p6o.png)
![4=k(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7l9c0mcs9z1ewg2zysbbwevughzvqvkn0k.png)
![4=k](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3g8moiuj4uxu75gaky6qejjofed7pdxm3w.png)
So the constant is k which means the equation for any (x,y,z) is:
![y=4 \cdot (x)/(√(z))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d6hec0fdyr5clpc2wf12bqs41mmuabcg0h.png)
We want to know y when x=6 and y=9:
![y=4 \cdot (6)/(√(9))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ni9si3s0e5930a8orouinptssmfndbz52x.png)
![y=4 \cdot (6)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gohwf42j5w5rssruftbt42ar95wwbrhveg.png)
![y=4 \cdot 2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ekyok9t63uzc52vdwt9foyhmv4maumpmxn.png)
![y=8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/df4p6eserpksm1tcn9644g3i3rlflyg03l.png)